(untitled) (Mantichora. Italian Journal of Performance Studies, 2020)
Godard’s Histoire(s) du cinéma is a film realized using found footages between 1989 and 1998. It celebrates the "end" of the XXI century and of the artistic form which better represented it: cinema. This essay aims to investigate the idea of "apocalypse" as it emerges from the film, in light of Godard’s interpretation of such important historical moment.